(untitled) (Pakistan Journal of Science, 2022)
The usage of nanoparticles in veterinary/animal production is still relatively new, yet they have long been used as therapeutic and/or diagnostic tools in human medicine. At the moment, improvements and breakthroughs in animal production are being made using nanotechnology advancements. Therefore, the goal of the current review is to provide a data-ailed classification and uses of nano-particles in animal science. By increasing therapeutic benefits and minimizing side effects, the creation of an alternative medicine delivery system based on nanoparticles is thought to be beneficial for treating microbial illnesses. The increasing applications of nanoparticles in veterinary medicine, reproductive technology, food delivery, biocide, and as a factor in meat, egg, and milk quality has been widely studied and found to be a noteworthy effect. Recently, the introduction of novel, small-scale technologies, and materials that are advantageous to livestock species has revolutionized practically most aspects of veterinary care and animal research. This review will cover information about varying types of nanoparticles, the benefits of using nanomaterials over their alternatives, and the nanotechnology role and applications in veterinary science. The use of nanoparticles to create nano-vaccines and nano-adjuvants, and their usage in gene therapy and cancer treatment has ushered in a new era of medicine. Moreover, there is also limited literature available on the use and possible effects of nanoparticles in poultry feed, hence, this review will highlight the promising effect of various mineral nanoparticles (NPs) or mineral supplements on the production performance of broiler and commercial layers.